Coupled Ionic–Electronic Charge Transport in Organic Neuromorphic Devices (Adv. Theory Simul. 6/2022). Issue 6 (10th June 2022) - Felder, Daniel; Femmer, Robert; Bell, Daniel; Rall, Deniz; Pietzonka, Dirk; Henzler, Sebastian; Linkhorst, John; Wessling, Matthias
Abstract : Coupled IonicElectronic Charge Transport in Organic Neuromorphic Devices In article number 2100492, Daniel Felder, John Linkhorst, Matthias Wessling, and co‐workers describe the non‐ideal behavior of organic neuromorphic devices by finite volume simulation. The models reveal impurities to cause device memory degradation and write errors through parasitic electrochemical reactions. These results enable mitigation strategies towards robust neural networks on highly efficient neuromorphic hardware.